Manajemen Kesiswaan Dalam Meningkatkan Prestasi Peserta Didik Melalui Ekstrakurikuler - Rizal Daeng Wibisono; Romi Siswanto (THE JOER: Journal Of Education Research, 2022)
Basically, good student management in an effort to develop talents and interests in realizing student achievement is something that is needed in every educational unit. The background of this research is as an effort to improve student management in an effort to achieve student achievement. A good madrasa is a madrasa that is able to print students into outstanding students in academic and non-academic fields. The focus of the problem in this study is 1) How to plan extracurricular activities to improve student achievement, 2) How to implement extracurricular activity programs to improve student achievement, 3) How to evaluate extracurricular activity programs to improve achievement. Meanwhile, the purpose of this research is to describe the planning, implementation, evaluation of the program and the implications of student management in improving student achievement at Madrasah Aliyah Negeri 6 Jombang. The study used qualitative methods with data collection techniques of participation observation, interviews, and documentation. In checking the validity of the data, researchers used triangulation. The results of this study can be seen that the planning of extracurricular activities has been implemented very well in the preparation of programs which include a) Islamic character formation, b) Improving extracurricular achievement. The implementation of extracurricular activities includes: a) Continuous coaching, b) Camping (outdoor activities), c) Conducting selections, d) Sending contingents outside the madrasa as representatives of the madrasa. The evaluation is carried out systematically, from the coach to the head of the front group, from the head of the front group to the Waka Kesiswaan, and finally from the Waka Kesiswaan to the head of the madrasa. The implications include: 1) for students in training students' skills and independence, 2) helping students to enter lectures, 3) Madrasas are known to the wider community for their non-academic achievements.